Selective LC-MRM/SIM-MS based profiling of adrenal steroids reveals metabolic signatures of 17α-hydroxylase deficiency. Issue 198 (April 2020) - Lee, Chaelin; Kim, Jung Hee; Moon, Sun Joon; Shim, Jaeyoon; Kim, Hugh I.; Choi, Man Ho
Graphical abstract: Highlights: A selective LC–MS-based profiling method of 27 serum adrenal steroids was developed. The assay enables high-throughput sample analysis using a <2-μm-particle LC column. The metabolic signatures of 17α-hydroxylase deficiency were obtained. The method might be used to discriminate subtypes of adrenal diseases. Abstract: Adrenal steroids are generated in the adrenal cortex and metabolized by various enzymes such as hydroxylases, dehydrogenases, and reductases. Determining the comprehensive metabolic signatures of adrenal steroids can provide insight into their metabolic functions and roles in the pathophysiology of adrenal diseases, including Cushing's syndrome (CS) and congenital adrenal hyperplasia (CAH). To this end, we developed an advanced quantitative profiling method of serum adrenal steroids with liquid chromatography-mass spectrometry (LC–MS) under molecular-specific scan modes. Twenty-seven steroids were separated on a 1.9-μm particle C18 column (50 × 2.1 mm) at a flow rate of 250 μL/min and quantified via triple-quadrupole MS with electrospray ionization. During validation, linearities ( r 2 ) were higher than 0.940 with a limit of quantification of 0.1–5.0 ng/mL, and precision (coefficient of variation) and accuracy (%bias) of 3.7–14.3 % and 96.3–113.1 %, respectively. In contrast with the significantly increased serum levels of mineralocorticoids ( P < 0.001), the present LC–MS assay revealed remarkably decreased levels of all glucocorticoids and androgens in a patient diagnosed with 17α-hydroxylase deficiency CAH ( P < 0.001) compared to those of age- and sex-matched healthy and CS subjects. In the CAH patient, the metabolic ratios for 17α-hydroxylase were significantly decreased, whereas there was no reduction in the metabolic ratio of 17-hydroxyprogesterone to androstenedione, indicating 17, 20-lyase activity. In particular, both pregnenolone and dehydroepiandrosterone sulfates, and their metabolic ratio, were identified as potential biomarkers for 17α-hydroxylase deficiency (all P < 0.001), which were also distinct from those of CS patients. The devised LC–MS assay clearly revealed the metabolic signatures of 17α-hydroxylase deficiency, as a rare phenotype of CAH, compared to both healthy and CS subjects, indicating its utility for screening adrenal diseases.